PENGARUH STRUKTUR MODAL DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTI DI BEI - Cut Fira Humaira; Tuti Meutia; Mayang Murni (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of Capital Structure and Corporate Social Responsibility (CSR) Disclosure on Company Value in Property Companies on the Indonesia Stock Exchange. The object of this study is a Property Company, the sampling technique uses saturated sampling. The data collection method comes from the Company's history, namely financial data that has been audited by a property company listed on the Indonesia Stock Exchange. The data analysis method used in this study is multiple regression analysis by operating SPPS Software. The results of this study indicate that the variables of the influence of capital structure and CSR disclosure on Company Value in Property Companies on the IDX for the period 2014-2023, it can be concluded that partially the capital structure has a positive and significant effect on company value, while CSR disclosure has a negative and significant effect on company value. And simultaneously the capital structure and CSR disclosure have a significant effect on Company Value in Property Companies. The limitations of this study include the research period only focusing on 10 property companies listed on the Indonesia Stock Exchange according to the criteria that have annual reports for the last 10 years. Thus limiting the results in general because they may not represent other companies. Thus limiting the results in general because they may not represent other companies. The data used are secondary data and do not cover internal information as well as policies and strategies in each company accurately. And for further research, it is recommended that the focus be expanded by collecting data from a longer period and various sources, including primary data through interviews and surveys. In addition, research should include case studies on several companies in the same or different sectors to increase the generalizability of the results.